2022
DOI: 10.1080/10824669.2022.2102982
|View full text |Cite
|
Sign up to set email alerts
|

Familiar Faces in High School: How Having the Same Peers from Year-to-Year Links to Student Absenteeism

Abstract: Student absenteeism is a persistent concern in K-12 education. Not only are the negative academic and social consequences of excessive absenteeism well documented, but states, districts, and schools are increasingly being held accountable for student attendance. As research indicates that disruptions in students' learning contexts may exacerbate absenteeism, peer consistency shows promise as a force for improving student attendance. This article examines whether having familiar faces, or consistent classmates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 57 publications
0
1
0
Order By: Relevance
“…Our findings scratch the surface of potential explorations around the use of high school coursework to reengage students in better attendance behaviors. Future research should consider the role of peer dynamics in the endorsement pathway framework in Texas and in states with similar graduation structures (Kirksey & Gottfried, 2018;Kirksey & Elefante, 2022). Moreover, STEM and STEM-CTE coursework throughout Texas and the U.S. continue to have limited availability given staffing and overall resource shortages, but previous research has shown the promise of having solid school transportation infrastructure in place to improve student attendance and access to courses (Gottfried, 2017).…”
Section: Future Researchmentioning
confidence: 99%
“…Our findings scratch the surface of potential explorations around the use of high school coursework to reengage students in better attendance behaviors. Future research should consider the role of peer dynamics in the endorsement pathway framework in Texas and in states with similar graduation structures (Kirksey & Gottfried, 2018;Kirksey & Elefante, 2022). Moreover, STEM and STEM-CTE coursework throughout Texas and the U.S. continue to have limited availability given staffing and overall resource shortages, but previous research has shown the promise of having solid school transportation infrastructure in place to improve student attendance and access to courses (Gottfried, 2017).…”
Section: Future Researchmentioning
confidence: 99%